Given
Graph
Find
Exponential equation for the graoh
Step-by-step explanation
Exponential equation is in the form of
![y=ab^x](https://img.qammunity.org/2023/formulas/mathematics/high-school/hye5rg1h8wj3ohgdt4j1vpepdhoym0w9ex.png)
from graph, we see
when x = 0 then y = -3
and when x = -1 then y = -6
now substitute these points in equation ,
(0 , -3) and (-1 , -6)
![\begin{gathered} -3=a(b)^0 \\ a=-3 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/6rh4f5mnj62epzmlapuelqnrcad8g15y2b.png)
and
![\begin{gathered} -6=-3b^(-1) \\ 2=b^(-1) \\ b=(1)/(2) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/pkef6jpm8m7aobq9f2ro51nibvi9aeryzt.png)
so , equation is
![y=-3((1)/(2))^x](https://img.qammunity.org/2023/formulas/mathematics/college/teou2ib0ndsn8feksdaiast96tv8gepfio.png)
Final Answer
Therefore , the exponential equation for the graph is
![y=-3((1)/(2))^x](https://img.qammunity.org/2023/formulas/mathematics/college/teou2ib0ndsn8feksdaiast96tv8gepfio.png)